The impact of principal administration on elementary school teachers' performance - Liza Krisdiani; Riswandi Riswandi; Rochmiyati Rochmiyati (Lighthouse Publishing, 2021)
The problem of this research is regarding the management of the principal on the performance of educators. The purpose of this study is to explore how principals should work in schools. Six efforts that can be made by principals in improving teacher performance include (1) a serious focus on improving teacher competence, (2) providing sufficient funds to increase teacher professionalism, (3) supervising and guiding teachers professionally, (4) creating a culture of school organization that is comfortable for teachers, (5) creates innovation and progress in schools, and (6) provides various awards for every achievement made by teachers. Therefore, it is recommended that principals be more active and creative in collaborating with teachers and stakeholders in teacher performance education. The research uses quantitative research methods, namely to see the partial effect between the variables in the survey with a quantitative approach. The population and sample of this study were elementary school teachers at SDN 1 Sumber Agung, Kemiling District, Bandar Lampung City. Data collection techniques used non-test techniques (observation, interviews, and documentation) and test techniques (Questionnaire). The data analysis technique used instrument validity test, instrument reliability test, instrument difficulty level, and differentiating power.